PENGARUH KARAKTERISTIK INDIVIDU, PENDIDIKAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP KEBERANIAN AKAN RESIKO MINAT BERWIRAUSAHA: THE EFFECT OF INDIVIDUAL CHARACTERISTICS, ENTREPRENEURSHIP EDUCATION AND FAMILY ENVIRONMENT WITH COURAGE ON ENTREPRENEURSHIP INTEREST RISK - muhammad rifki (LPPM Universitas Lembah Dempo, 2022)
This research focuses on Micro, Small and Medium Enterprises (MSMEs) in the KINARI AHAD market. This research was conducted using a descriptive type of research with a quantitative approach. The population of this study were all permanent respondents, amounting to 28 people. In this study the authors took the sampling that is using a total sampling technique of 28 respondents. The results of the multiple linear regression analysis carried out obtained the regression equation Y = 36.708 + 0.436X1 + 0.004 X2 + 0.264 X3, meaning that it can be said that the independent variables, namely individual characteristics, entrepreneurship education and family environment together have a positive directional relationship with courage to risk. interest in entrepreneurship The results of the F test obtained the fcount value of 57.413 and the ftable value of 3.17. This means that from these results it can be seen that the value of fcount > ftable (57.413 > 3.17) states that individual characteristics, entrepreneurship education, and family environment have a very significant influence on the courage to risk interest in entrepreneurship. (Y) 68.4%, while the remaining 31.6% is influenced by other variables not included in this study. Keywords: Individual Characteristics, Entrepreneurship Education and Family Environment with Courage to Risk Interest in Entrepreneurship This research focuses on Micro, Small and Medium Enterprises (MSMEs) in the KINARI AHAD market. This research was conducted using a descriptive type of research with a quantitative approach. The population of this study were all permanent respondents, amounting to 28 people. In this study the authors took the sampling that is using a total sampling technique of 28 respondents. The results of the multiple linear regression analysis carried out obtained the regression equation Y = 36.708 + 0.436X1 + 0.004 X2 + 0.264 X3, meaning that it can be said that the independent variables, namely individual characteristics, entrepreneurship education and family environment together have a positive directional relationship with courage to risk. interest in entrepreneurship The results of the F test obtained the fcount value of 57.413 and the ftable value of 3.17. This means that from these results it can be seen that the value of fcount > ftable (57.413 > 3.17) states that individual characteristics, entrepreneurship education, and family environment have a very significant influence on the courage to risk interest in entrepreneurship. (Y) 68.4%, while the remaining 31.6% is influenced by other variables not included in this study. Keywords: Individual Characteristics, Entrepreneurship Education and Family Environment with Courage to Risk Interest in Entrepreneurship